2020
DOI: 10.1002/aenm.201903724
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Electrode Materials Comprising of Structure‐Engineered Quantum Dots for High‐Performance Asymmetric Micro‐Supercapacitors

Abstract: Micro‐supercapacitors (MSCs) as a new class of energy storage devices have attracted great attention due to their unique merits. However, the narrow operating voltage, slow frequency response, and relatively low energy density of MSCs are still insufficient. Therefore, an effective strategy to improve their electrochemical performance by innovating upon the design from various aspects remains a huge challenge. Here, surface and structural engineering by downsizing to quantum dot scale, doping heteroatoms, crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 67 publications
0
37
0
Order By: Relevance
“…k) Comparison of the areal energy density of the constructed symmetric MSC‐CP with that of other high‐performance asymmetric MSCs reported previously. [ 8,11,15–22,62,73–81 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…k) Comparison of the areal energy density of the constructed symmetric MSC‐CP with that of other high‐performance asymmetric MSCs reported previously. [ 8,11,15–22,62,73–81 ]…”
Section: Resultsmentioning
confidence: 99%
“…Impressively, the specific areal capacitance of the MSC‐CP was calculated to be 66.1, 63.8, 54.4, 49.7, and 47.1 mF cm −2 at scan rates of 10, 20, 50, 80 and 100 mV s −1 , with corresponding specific volumetric capacitances of 44.4, 42.8, 36.5, 33.3, and 31.6 F cm −3 , respectively (Figure S19d,e, Supporting Information). Thanks to the 2.3 V operating voltage enabled by the HVTT‐PAM‐10.5, the MSC‐CP achieved a record high areal energy density of 48.6 μWh cm −2 at the power density of 760.2 μW cm −2 , far outperforming all reported symmetric MSCs with aqueous electrolytes based on carbon materials, [ 12,25–27,43–61 ] conductive polymers, [ 13,62–64 ] MXene, [ 14,65–68 ] metal oxides, [ 69–72 ] (Figure 4e; Table S1, Supporting Information) and high‐energy AMSCs with aqueous electrolytes [ 8,11,15–22,62,73–81 ] (Figure 4k; Figure S19g and Table S1, Supporting Information). Even if the power density was increased to 5416.5 μW cm −2 , a high energy density of 34.6 μWh cm −2 was still maintained.…”
Section: Resultsmentioning
confidence: 99%
“…Clearly,t he peaks at 532.6, 531.6, and 533.1 eV belong to the B À Ob ond, O = Cb ond, and O À Cb ond, respectively,which is highly consist with B1sand C1sspectra of ABCNs. [31] Thecrystalline structure of ABCNs is evaluated by X-ray diffraction (XRD). TheX RD spectrum of g-C 3 N 4 in boron nanosheets are shown in the Supporting Information, Figure S14.…”
Section: Resultsmentioning
confidence: 99%
“…One strategy is to make capacitive asymmetric MSCs with both EDLC and pseudocapacitor materials. For example, Liu et al 118 reported an asymmetric MSC using nitrogen-doped graphene quantum dots (N-GQDs) as negative electrode and molybdenum disulfide quantum dots (MoS 2 -QDs) as positive electrode, and achieved a large operating voltage up to 1.5 V and a high energy density of 0.55 mWh cm −3 . In addition, Gao et al 61 prepared an integrated MSC array based on MnO 2 @Ppy@MWCNT (multiwalled carbon nanotube) anode and Ppy@MWCNT cathode.…”
Section: Asymmetric Mscsmentioning
confidence: 99%